2010
DOI: 10.1117/12.840185
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz dynamics of ionic liquids from a combined dielectric relaxation, terahertz, and optical Kerr effect study: evidence for mesoscopic aggregation

Abstract: To exploit the great potential of room-temperature ionic liquids (RTILs) as solvents that offer both low environmental impact and product selectivity, an understanding of the liquid structure, the microscopic dynamics, and the way in which the pertinent macroscopic properties, such as viscosity, thermal conductivity, ionic diffusion, and solvation dynamics depend on these properties, is essential. We have measured the intermolecular dynamics of the 1,3-dialkylimidazolium- and [bmim][DCA], at 25 °C from below 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…relaxation times τ sub−α > τ α . Whilst the sub-α mode largely dominates the OKE signal it is hardly discernible in the dielectric spectrum (Figure 3) [12,37]. In marked contrast, the sub-α relaxation cannot be detected the spectra of pyrrolidinium-, pyridinium-and sulfonium-RTILs.…”
Section: General Remarksmentioning
confidence: 93%
See 2 more Smart Citations
“…relaxation times τ sub−α > τ α . Whilst the sub-α mode largely dominates the OKE signal it is hardly discernible in the dielectric spectrum (Figure 3) [12,37]. In marked contrast, the sub-α relaxation cannot be detected the spectra of pyrrolidinium-, pyridinium-and sulfonium-RTILs.…”
Section: General Remarksmentioning
confidence: 93%
“…Already published material can be found in Refs. [12,33,34,35,36,37,38,39]. From a review of these results the general characteristics discussed below can be observed.…”
Section: General Remarksmentioning
confidence: 94%
See 1 more Smart Citation
“…Besides the above mentioned work, there exists a large body of dielectric as well as light scattering studies that analyze high frequency spectra in detail, [23][24][25][26][27][28][29] where most of the studies use a similar analysis approach combining several relaxation and damped oscillator models, often using more than 4 model functions. In particular when the liquids are cooled to the point where the main relaxation peak shifts out of the frequency window of the used methods, 13,14,19,20,[30][31][32] the full complexity of the high frequency dynamics is revealed and a minimum between the main relaxation peak and the microscopic peak is observed.…”
Section: Fit Proceduresmentioning
confidence: 99%
“…Many experimental techniques such as small-angle X-ray scattering (SAXS), 8 small-angle neutron scattering (SANS), 9 dielectric spectroscopy, 10,11 NMR, 12,13 fluorescence, 14,15 optical Kerr effect spectroscopy, 10,16 and also molecular dynamics (MD) simulation studies 17 have been exploited to understand the structure and dynamics of RTILs. Among these, studies based on steady state and time-resolved fluorescence have been proved to be quite useful in probing the structural organization of RTILs.…”
Section: Introductionmentioning
confidence: 99%